Click It: The Effect of Integrating Socrative and KWL on Students’ Academic Reading Comprehension - Dewi Nur Suci; Merliyani Putri Anggraini; Ary Ningrum; Inas Nadifah; Qoidatul Marhumah (Journal of Languages and Language Teaching, 2023)
Socrative as one of educational technologies provides the students an ease to learn language through reading activities. They can practice reading on screen as the students in global era have commonly familiarized with. However, the teacher can apply certain reading strategies for students’ understandings on materials when trying to integrate technology for reading. Thus, this research proposes to investigate the effectiveness of Socrative and Moodle in reading classrooms that employ Kow-Want to Know-Learned (KWL) strategy. By using causal comparative study, seventy students of English Department at one of Islamic state universities in East Java Indonesia who are in the third semester are divided into intervention and control groups. The previous group is directed to read by using Moodle and do quiz with Socrative, while the latter read and do the quiz in Moodle. Here, KWL strategy is integrated with both technologies. The results of study exemplify that there is no significance difference between the students in the intervention and the control group. However, the mean scores of posttest on the intervention group increased better than the control group.